Pembekalan Keterampilan Mobile Video Editing Menggunakan Kinemaster untuk Siswa-siswi SMAK Penabur Summarecon Bekasi - Muhammad Dicka Ma’arief Alyatalatthaf (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
Information and Communication Technology (ICT) is developing so rapidly. Almost all people needs in this 4.0 era can be fulfilled in just one hand (smartphone). One of them is creative content fields, especially audio visuals. SMAK Penabur Summarecon Bekasi sees this potential and presents the opportunity in the Content Creator extracurricular (Ekskur) for students who have high interest in the creative content industry.